EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER DENGAN PENDEKATAN ILMIAH (NHT-PI) DAN TEAM ASSISTED INDIVIDUALLIZATION (TAI) PADA MATERI POKOK BARISAN DAN DERET DITINJAU DARI GAYA BELAJAR SISWA KELAS XI SMK NEGERI SE-KABUPATEN KLATEN - Nurhayati, Ambar; Mardiyana, Mardiyana; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this study were to determine: (1) which gives better learning achievement, NHT-PI type, the type of TAI, or direct instruction learning model (2) which is learning achievement better, students who have a visual, auditory or kinesthetic learning style (3) In each type of learning model, which better learning achievement, students who have a visual learning style, auditory or kinesthetic (4) In each learning style, which is learning achievement better, students who applied learning models NHT-PI, TAI, or direct instruction learning. This study was a quasi exsperimental research. The sample of research consisted of 280 students: 90 students in experiment 1 class, 90 students in experiment 2 class, and 100 students in control class. The data was taken from the result of mathematics learning achievement test and student learning style questionnaire. The data obtained was then analyzed using a two-way ANAVA with unbalanced cells. Considering the result of hypothesis testing, the following conclusions could be drawn. (1) The learning achievement of the students treated with NHT-PI type of learning model was better than that of those treated with TAI type and direct learning; that of those treated with TAI was same as that of those treated with direct learning. (2) The learning style did not provide significant difference in learning achievement. (2)Â Either in NHT-PI and TAI types of cooperative learning model or in direct learning, the different learning style did not provide significantly different learning achievement. (4) In the students with visual learning style, the three learning models did not provide significantly different learning achievement; in the students with auditory learning style, NHT-PI was as good as the TAI types, the TAI type was a good as the direct learning, and NHT-PI was better than the direct learning; in the students with kinesthetic learning style, the three learning model had equal effectiveness.Â Keywords: Numbered Head Together Scientific Methode Approach (NHT-PI), Team Assisted Individuallization (TAI), Student Learning Style